2019
DOI: 10.1111/nph.15817
|View full text |Cite
|
Sign up to set email alerts
|

Field crop phenomics: enabling breeding for radiation use efficiency and biomass in cereal crops

Abstract: Summary Plant phenotyping forms the core of crop breeding, allowing breeders to build on physiological traits and mechanistic science to inform their selection of material for crossing and genetic gain. Recent rapid progress in high‐throughput techniques based on machine vision, robotics, and computing (plant phenomics) enables crop physiologists and breeders to quantitatively measure complex and previously intractable traits. By combining these techniques with affordable genomic sequencing and genotyping, mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(111 citation statements)
references
References 147 publications
1
109
0
1
Order By: Relevance
“…Aerial imaging is proposed as a promising strategy to estimate the canopy photosynthesis and thereby light utilization on a spatial and temporal scale by multispectral-sensing. The advancement of these techniques will, together with genomics, facilitate a more efficient selection of source parameters and thereby accelerate progress in the final yield (Furbank et al, 2019).…”
Section: Relevance Of Gcd For Breedingmentioning
confidence: 99%
See 1 more Smart Citation
“…Aerial imaging is proposed as a promising strategy to estimate the canopy photosynthesis and thereby light utilization on a spatial and temporal scale by multispectral-sensing. The advancement of these techniques will, together with genomics, facilitate a more efficient selection of source parameters and thereby accelerate progress in the final yield (Furbank et al, 2019).…”
Section: Relevance Of Gcd For Breedingmentioning
confidence: 99%
“…Complementary crosses between genotypes with high sink capacity and those with high source capacity resulted in progeny with substantial yield improvement (Reynolds et al, 2017), suggesting the co-limitation of source and sink on yield. It has been suggested that the selection of crossing partners based on physiological traits is a promising strategy to achieve a higher crop productivity via breeding, which is not least facilitated by the increasingly automated phenotyping techniques Reynolds and Langridge, 2016;Reynolds et al, 2017;Furbank et al, 2019). A precise description of the sink and source characteristics of possible genetic resources for future winter wheat varieties is, together with the application of genomic tools, a purposive strategy to promote the genetic gain via strategic complementary crosses.…”
Section: Introductionmentioning
confidence: 99%
“…The strong influence of environment and measurement conditions on canopy temperature is evident from this and other studies. While high heritability of canopy temperature has been reported previously in other crops, they have relied largely upon cooled thermal cameras that can only be carried aboard manned aircraft [43]. Issues associated with lightweight uncooled thermal cameras, such as thermal drift and non-uniformities in images have been reported extensively along with statistical models for correction [44].…”
Section: Discussionmentioning
confidence: 99%
“…The current study was conducted on the flag leaf and scaling leaf-level data to the canopy can be complicated as leaf age and leaf angle can play a crucial role when integrating leaf level photosynthetic traits at the canopy scale 67 . However, leaf level measurements have been previously associated with higher yields [68][69][70] and in the present study, traits measured at leaf level explained a significant proportion of the variation of BM_PM, HI, TGW, GM2 and RUE measured at different growth stages.…”
Section: Implications In Physiological Breedingmentioning
confidence: 99%